Relationship between Employees’ Perceptions of External CSR and Organizational Identity - Bista, Sita (Nepal Journal of Multidisciplinary Research, 2022)
The purpose of this study was to evaluate correlation between external corporate social responsibility (external CSR for community, environment and customers) and organizational identity. The data were collected from 288 respondents (employees) from five commercial banks of Nepal through cross sectional survey questionnaires. The results show that there is significant and positive correlation between external CSR and organizational identity.